Spiritual Transformation of the Main Character in the Tarung Sarung Movie - Aisyah, Siti; Agung Prasongko, Wahyu; Arif Roziqin, Muhamad (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2024)
One of the current phenomenal issues being widely discussed by the public is the disbelief in the existence of God (atheism). The issue of atheism is addressed in the film "Tarung Sarung." The purpose of this research is to understand the reasons behind Deni Ruso, an atheist, becoming a devout follower of Islam, as well as the process of Deni Ruso's spiritual transformation. This research adopts a qualitative research approach and utilizes semiotic analysis as the method. The results of this study indicate that the underlying causes for the main character's transformation from being an atheist to a devout follower of Islam are as follows: firstly, friendship. Through friendship, emotional support and inspiration can be provided. When someone has friends who are involved in spiritual practices, it can serve as a motivator for embarking on a spiritual journey independently. Secondly, the environment that facilitates access to places of worship and meditation practices can influence individuals to actively engage in spiritual exercises. Thirdly, the experience of deep love can open one's heart and mind to a deeper spiritual dimension. Furthermore, the process of spiritual transformation experienced by the main character involves self-awareness that God plays a significant role in life, as well as believing in religion as a guide for behavior and regulating all aspects to attain tranquility in both worldly life and the hereafter.